"Ulysses syndrome". A journey from literature to social (Polis (Santiago), 2018)
Óscar Robledo’s essay transports us to a very different París to that of the postcards, one in which world’s missery lives side by side with the opulence of the ‘succesfull’. A beatifull and brilliant city in which the semiproletarized bodies of latin american students and so many other inmigrants walk arround; the same who  live in twelve square meters and who fight loneliness, hunger and precariousness through the heat of their bodies and almost frantic sexual encounters. Beyond common places and stereotipes, the description of the lifes of these beings inserted in one of the most rich cities of the world, is a cronical of underdevelopment in the core of a country who invented luxury. It is the story of so many dreamers eager for a culture which barely admits them with the indiference of those who feel themselves part of a ‘higher’ civilization.
Keywords: Paris; precariousness; globalization; youth; literature